What’s new in psoriasis treatment? An analysis of systematic reviews published in 2015 - Foulkes, A.C.; Ferguson, F.; Grindlay, D.J.C.; Williams, H.C.; Griffiths, C.E.M.; Warren, R.B. (Wiley, 2018)
This review provides a summary of key findings from 27 systematic reviews of 51 articles first published or indexed during 2015, focusing on the treatment of psoriasis as well as precision medicine in psoriasis. Evidence supports weight loss interventions by dieting and exercise for the improvement in disease severity in overweight and obese patients with psoriasis. No significant increased risk of serious infections were reported for the biologic therapies adalimumab, etanercept and ustekinumab when compared with appropriate comparators. Evidence could not provide reliable estimates of rare adverse events, underscoring the need for large prospective registries. Polymorphisms in the tumour necrosis factor (TNF) alpha gene may confer improved responses to TNF inhibitor (TNFI) therapy, but studies to date lack power to detect true association. From limited available evidence, multidisciplinary management is both more effective and more satisfactory for patients with psoriasis and psoriatic arthritis than conventional consultations. This summary of reviews provides a succinct guide for clinicians and patients wishing to remain up‐to‐date with high quality evidence for the treatment of psoriasis.